2013
DOI: 10.3171/2013.7.jns122417
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of CD133-positive glioma cells in recurrent de novo glioblastomas after radiotherapy and chemotherapy

Abstract: Object. Recent evidence suggests that a glioma stem cell subpopulation may determine the biological behavior of tumors, including resistance to therapy. To investigate this hypothesis, the authors examined varying grades of gliomas for stem cell marker expressions and histopathological changes between primary and recurrent tumors.Methods. Tumor samples were collected during surgery from 70 patients with varying grades of gliomas (Grade II in 12 patients, Grade III in 16, and Grade IV in 42) prior to any adjuva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 34 publications
3
60
0
Order By: Relevance
“…In the latter study, a considerable proportion of tumors contained >10% or even >25% of AC133 þ cells. Furthermore, the frequencies of CD133 þ glioma cells and their proliferation seem to increase considerably at GBM recurrence (41). AC133 þ tumor stem cells could perhaps also be targeted in brain tumors other than GBM.…”
Section: Ac133âcd3 Bsab Does Not Affect Hscs At Concentrations Effectmentioning
confidence: 99%
“…In the latter study, a considerable proportion of tumors contained >10% or even >25% of AC133 þ cells. Furthermore, the frequencies of CD133 þ glioma cells and their proliferation seem to increase considerably at GBM recurrence (41). AC133 þ tumor stem cells could perhaps also be targeted in brain tumors other than GBM.…”
Section: Ac133âcd3 Bsab Does Not Affect Hscs At Concentrations Effectmentioning
confidence: 99%
“…Interestingly, Singh et al (2003) found CD133 + cells to be tumor initiating, whereas CD133 À cells could not initiate a tumor or self-renew in a mouse xenograft model [118,121]. The levels of CD133 + BTSCs has since been correlated to negative prognoses in gliomas, and have been found to be particularly enriched in recurrent tumors after radiation and chemotherapy [122][123][124]. These findings highlight the importance of stem cells in the overall initiation, malignancy, and recurrence of brain tumors.…”
Section: The Role Of Astrocytes In Brain Tumor Stem Cell Biologymentioning
confidence: 99%
“…And CSCs model provides an explanation for the resistance to chemotherapy in some type of tumors [6] . Expression of CD133 in glioblastoma cell population increased after radiation therapy, whether in glioma cell lines or in nude mice [7] . Therefore, strategies that aim to CSCs are of particular interest in cancer therapy [8] .…”
Section: Introductionmentioning
confidence: 99%